Nobility and Land System in the Pre-Colonial Era of the Surakarta and Yogyakarta Kingdoms (Paramita: Historical Studies Journal, 2020)
This article discusses apanage land belonging to the village heads, which is a legacy of the land system in the era of pre-colonial Surakarta and Yogyakarta kingdoms or what is termed as Vorstenlanden. This paper is aimed to find out how the feudal and nobility system in Java, which in the colonial era was very vulnerable to intervention and politics of splitting or fighting. To answering this question, a study will be conducted on the history of the Islamic Mataram kingdom until the era of Surakarta and Yogyakarta, en focusing on the analysis of the apanage and nobility systems. The method used is a historical method that consists of four steps, namely, heuristics, textual criticism, interpretation, and historiography. This research shows high officials and royal aristocrats have the power and the right to collect land tax and labor. A decline in the degree of nobility in Java will also affect the extent or amount of apanage land obtained. In the other side, the peasant only enjoy a small portion of the results of working on land or rice fields. Artikel ini membahas tentang tanah apanage milik para kepala desa yang merupakan     peninggalan sistem pertanahan di era pra-kolonial kerajaan Surakarta dan Yogyakarta atau yang disebut dengan Vorstenlanden. Tulisan ini bertujuan untuk mengetahui bagaimana sistem feodal dan bangsawan di Jawa yang pada masa penjajahan sangat rentan terhadap intervensi dan politik perpecahan atau perkelahian. Untuk menjawab pertanyaan tersebut, dilakukan studi tentang sejarah kerajaan Mataram Islam hingga era Surakarta dan Yogyakarta, dengan fokus pada analisis sistem bangsawan dan bangsawan. Metode yang digunakan adalah metode sejarah yang terdiri dari empat tahapan yaitu heuristik, kritik tekstual, interpretasi, dan historiografi. Penelitian ini menunjukkan pejabat tinggi dan bangsawan kerajaan memiliki kekuasaan dan hak untuk memungut pajak tanah dan tenaga kerja. Penurunan derajat kebangsawanan di Jawa juga akan mempengaruhi luasan atau jumlah rata-rata tanah yang diperoleh. Di sisi lain, petani hanya menikmati sebagian kecil dari hasil menggarap lahan atau sawah.